The Effectiveness of the STEM Integrated PBL Model on Science Collaboration and Problem-Solving Skills - Mohamad Ismail; Budi Utami; Kadek Dwi Hendratma Gunawan; Suciati Suciati; Bramastia Bramastia (Universitas Negeri Semarang, 2025)
This study aimed to examine the effect of the Problem-Based Learning (PBL) model integrated with STEM on students’ collaboration and problem-solving skills. It employed a quasi-experimental method using a pretest-posttest control group design. The population included all seventh-grade students of SMP Negeri 1 Plupuh in the 2024/2025 academic year. The sample was selected through cluster random sampling, with Class VII C designated as the experimental group and Class VII D as the control group. Data were collected through tests, observations, and documentation. The data were analyzed using an independent t-test with a significance level of 0.05. The analysis revealed that the STEM-integrated PBL model had a significant effect on students’ problem-solving skills, with a significance value of 0.028 (< 0.05), because this learning provides a holistic, real, collaborative learning experience and encourages higher-level thinking. While the collaboration skills showed a significance value of 0.011 (< 0.05) because the learning process emphasizes group work in solving real problems, thus encouraging interaction, shared responsibility, productive communication, and positive interdependence between group members. These findings indicate there is an effect of implementing Problem Based Learning (PBL) integrated with Science, Technology, Engineering, and Mathematics (STEM) on students’ collaboration and problem-solving skill. Problem Based Learning (PBL) integrated STEM allows students to broaden their horizons, discuss and collaborate in problem solving, encourage students to refine their knowledge through discussion, communicate in groups and respect each other when there are differences of opinion, critically assess group processes and work, provide feedback, and agree on the best solution, which directly improves various aspects of collaboration and develops competencies to address the complex challenges of their future.